2016
DOI: 10.1111/nph.13908
|View full text |Cite
|
Sign up to set email alerts
|

OsCLT1, a CRT‐like transporter 1, is required for glutathione homeostasis and arsenic tolerance in rice

Abstract: SummaryArsenic (As) contamination in a paddy environment can cause phytotoxicity and elevated As accumulation in rice (Oryza sativa). The mechanism of As detoxification in rice is still poorly understood.We isolated an arsenate (As(V))-sensitive mutant of rice. Genomic resequencing and complementation identified OsCLT1, encoding a CRT-like transporter, as the causal gene for the mutant phenotype.OsCLT1 is localized to the envelope membrane of plastids. The glutathione and cglutamylcysteine contents in roots of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 46 publications
1
53
0
1
Order By: Relevance
“…All transgenic rice lines were produced in the HJ2 or crd1 background. The rice plants were grown in a greenhouse and cultivated as previously described (Yang et al ., ). Arabidopsis plants were grown at 22°C with 16/8 h (light/dark) photoperiod at approximately 120 μmol m −2 sec −1 light (He et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…All transgenic rice lines were produced in the HJ2 or crd1 background. The rice plants were grown in a greenhouse and cultivated as previously described (Yang et al ., ). Arabidopsis plants were grown at 22°C with 16/8 h (light/dark) photoperiod at approximately 120 μmol m −2 sec −1 light (He et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…It is important to note that an aquaporin channel of TIP class (TIP4;1) is suggested to be involved in As(III) uptake in P. vittata in a recent study by He et al (2016). Yang et al (2016) identified a transporter OsCLT1 [CRT (Chloroquine-Resistance Transporter)-Like transporter) in rice, which is localized to plastids. The mutant lines (Osclt1) had decreased PC2 levels as compared to WT upon exposure to As(V) or As(III) and showed a decrease in As concentration.…”
Section: The Transport and Subcellular Distribution Of Arsenic: The Imentioning
confidence: 99%
“…MAN3 ( Endo‐β‐Mannanase 3 ) and ZAT6 ( Zinc‐Finger Transcription Factor 6 ) have been reported to regulate Cd tolerance through the GSH‐ and PC‐dependent pathway (Chen et al , , ). The rice CRT‐like transporter OsCLT1 mediates the export of γ ‐glutamylcysteine and glutathione from plastids to the cytoplasm for the synthesis of PCs; mutation of OsCLT1 results in hypersensitivity to both arsenic and Cd (Yang et al , ). Because of the demand on thiol compounds in Cd detoxification, exposure of maize roots to Cd markedly induced sulphate uptake by upregulating the expression of high‐affinity sulphate transporter genes (Nocito et al , , ), whereas tolerance of Cd is compromised under sulphur‐limiting conditions (Adhikari et al , ).…”
Section: Introductionmentioning
confidence: 99%